2016
DOI: 10.1002/fes3.79
|View full text |Cite
|
Sign up to set email alerts
|

Flood and drought tolerance in rice: opposite but may coexist

Abstract: Flood and drought are the two most prevalent abiotic stresses causing major yield reduction globally. In the last decade, molecular mechanisms of flood tolerance in rice have been revealed with successful release of flash flood-tolerant varieties to farmers. However, despite extensive research, the breakthrough of drought tolerance is still to come. In this review, we have examined the distribution and population types of drought-and flood-tolerant rice accessions, synthesized recent progresses of flood and dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 98 publications
(273 reference statements)
1
51
0
Order By: Relevance
“…Cellular dehydration caused by drought, and hypoxia driven by submergence, trigger a cascade of adaptive responses that are regulated at the molecular level in plants and are directed to maintain vital functions and protect structures from damage. Since cellular protection is a priority during stress, it has been shown that some responses to dehydration and excess water have common molecular effectors acting as nodes in the crosstalk between responses to drought and submergence [ 9 , 10 , 11 ]. This may have allowed wild plants to evolve tolerance mechanisms to cope with alternate drought and flooding events, which commonly occur consecutively in some regions of the world [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular dehydration caused by drought, and hypoxia driven by submergence, trigger a cascade of adaptive responses that are regulated at the molecular level in plants and are directed to maintain vital functions and protect structures from damage. Since cellular protection is a priority during stress, it has been shown that some responses to dehydration and excess water have common molecular effectors acting as nodes in the crosstalk between responses to drought and submergence [ 9 , 10 , 11 ]. This may have allowed wild plants to evolve tolerance mechanisms to cope with alternate drought and flooding events, which commonly occur consecutively in some regions of the world [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…These aus rice cultivars are early maturing, photoperiod insensitive and drought tolerant 8,11 . The genetic diversity among aus genotypes is abundant and they are enriched with various abiotic and biotic stress resistance genes 6,10,12,13 . For example, a traditional aus cultivar FR 13A harbour Sub1 gene which confers submergence tolerance 14,15 ; likewise Kasalath an aus type cultivar was the donor of Pstol1 gene which confers phosphorus starvation tolerance 13 .…”
Section: Introductionmentioning
confidence: 99%
“…BG1222 an aus type cultivars harbour xa34 bacterial blight resistance genes 24 . Most of the drought-tolerant rice are originated from aus rice germplasm which has been cultivated in Northeast India and Bangladesh 12,25 . Knowledge of the genetic diversity of rice genotypes is useful for core collection development and effective conservation strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier we analysed preferential distribution pattern and population types of drought and flood tolerant rice accessions (Bin Rahman and Zhang 2016 ). However, in this review, we analysed all seven major abiotic stresses along with one nutrient deficiency tolerance.…”
Section: Reviewmentioning
confidence: 99%